Towards a framework for the expansion of mobile computing in learning in Kuwaiti higher education: challenges and opportunities - Alturki, Abdullah (2017)
During the last few years, efficient mobile wireless communication devices have become widely available and easily accessible by a broad range of higher education students around the world in general and in Kuwait in particular. These devices offer the possibility of extending the boundaries of the educational process outside traditional classroom settings by providing communication and collaboration tools for students, instructors and staff members and by facilitating remote access to shared materials and tools. This learning arrangement is referred to as mobile learning or m-learning. The purpose of this thesis was to study and improve the use of m-learning in Kuwaiti higher education so learning in general would improve. This study aimed to develop a conceptual framework for guiding Kuwaiti decision makers in the successful adaptation of mobile learning in the Kuwaiti higher educational system. One of the major focuses of this study was to use mobile learning in places where it was intrinsically valuable such as subjects involving field studies. Three studies were conducted in Kuwait. In the first study, twenty-six instructors from three different Kuwaiti universities were interviewed to reveal the extent of the acceptance of the idea of mobile learning in Kuwaiti higher education. The second study was based on the results of the first study and used ninety-four students from five faculties at two universities to evaluate the trends of mobile learning amongst students and teachers. In the third study, there were forty participants from three faculties at two universities. This study tried to determine how beneficial it is to use a popular social media application as a learning tool under strict monitoring rules and instructions. Based on the results of the three studies conducted in this thesis, a framework was built to address the challenges and barriers facing mobile learning in Kuwait. This framework provides an appropriate environment for the adaptation of successful mobile learning in Kuwaiti higher education. The outcomes of the studies and research conducted for this thesis demonstrated that Kuwait could be a very successful example of adapting mobile learning if the barriers were faced by implementing the appropriate framework. The proposed framework enables Kuwait to be the one of the leaders of mobile learning in the surrounding region.